2021
DOI: 10.3389/fphys.2021.667278
|View full text |Cite
|
Sign up to set email alerts
|

Role of Podoplanin-Positive Cells in Cardiac Fibrosis and Angiogenesis After Ischemia

Abstract: New insights into the cellular and extra-cellular composition of scar tissue after myocardial infarction (MI) have been identified. Recently, a heterogeneous podoplanin-expressing cell population has been associated with fibrogenic and inflammatory responses and lymphatic vessel growth during scar formation. Podoplanin is a mucin-like transmembrane glycoprotein that plays an important role in heart development, cell motility, tumorigenesis, and metastasis. In the adult mouse heart, podoplanin is expressed only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 160 publications
(251 reference statements)
0
12
0
Order By: Relevance
“…Our understanding of mesenchymal heterogeneity is expanding exponentially, and advances in single-cell technologies have uncovered a wide spectrum of mesenchymal and endothelial phenotypes with specific functions and spatial distributions ( Suryawanshi et al, 2018 ; Takeda et al, 2019 ; Vijay et al, 2019 ). Mesenchymal heterogeneity can be used to spatially localise cells, identify cells involved in morphogenesis, angiogenesis or quiescence, and characterise inflammatory, anti-inflammatory, or invasive phenotypes ( Cimini and Kishore, 2021 ; Mezawa et al, 2019 ; Mezheyeuski et al, 2020 ; Nazari et al, 2016 ; Quintanilla et al, 2019 ). Dramatic advances in flow cytometry over the past few decades have enabled the simultaneous quantification of upwards of 30 antigens, allowing detection of in depth cell heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of mesenchymal heterogeneity is expanding exponentially, and advances in single-cell technologies have uncovered a wide spectrum of mesenchymal and endothelial phenotypes with specific functions and spatial distributions ( Suryawanshi et al, 2018 ; Takeda et al, 2019 ; Vijay et al, 2019 ). Mesenchymal heterogeneity can be used to spatially localise cells, identify cells involved in morphogenesis, angiogenesis or quiescence, and characterise inflammatory, anti-inflammatory, or invasive phenotypes ( Cimini and Kishore, 2021 ; Mezawa et al, 2019 ; Mezheyeuski et al, 2020 ; Nazari et al, 2016 ; Quintanilla et al, 2019 ). Dramatic advances in flow cytometry over the past few decades have enabled the simultaneous quantification of upwards of 30 antigens, allowing detection of in depth cell heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that lymphatic ECs are defined by the expression of typical markers, such as Prox1, LYVE-1, Flt4, and PDPN [21][22][23]. However, it is important to consider that even profibrotic α-SMA + fibroblasts have been demonstrated to express PDPN in a variety of disorders, including SSc-related cutaneous fibrosis and cardiac fibrosis [25,27], and that PDPN can be considered not only a reliable myofibroblast marker [24], but also a marker of aggressiveness in tumors, as this transmembrane glycoprotein promotes cancer cell migration and invasion, and is highly expressed in cancer-associated fibroblasts [26,28,29]. On this basis, we indeed considered the combination of PDPN and α-SMA markers unsuitable to search for Ly-EndMT in fibrotic skin sections, and thus chose LYVE-1 as the lymphatic EC-specific marker.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphatic ECs can be distinguished from blood vascular ECs by the expression of distinctive markers, such as podoplanin (PDPN), lymphatic vessel endothelial hyaluronan receptor-1 (LYVE-1), vascular endothelial growth factor receptor-3 (also known as Flt4), as well as the nuclear factor prospero-related homeobox protein 1 (Prox1), which is a main regulator of lymphatic vessel development [21][22][23]. Of note, activated profibrotic fibroblasts/myofibroblasts observed in a variety of disorders, including SSc-related cutaneous fibrosis, have been shown to express PDPN [24][25][26][27][28][29]. Furthermore, a significant reduction in the number of lymphatic microvessels correlating with the progression of tissue fibrosis has been described in skin lesions of SSc patients [19].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (17) also demonstrated that high PDPN expression in tissues reduces the sensitivity to adjuvant chemotherapy and correlates with poor prognosis of patients with gastric cancer. PDPN is a mucin-like transmembrane glycoprotein that is widely used as a marker for the lymphatic endothelium (18). PDPN expression in cancer cells has been reported in various tumor types, including brain tumors, esophageal squamous cell carcinoma, angiosarcoma, mesothelioma, squamous cell carcinoma of the lung and cervical carcinoma (19,20).…”
Section: Discussionmentioning
confidence: 99%